Papua Special Autonomic Fund Management Strategies in Sustainable Development Perspective in Papua - Eddy Way (Budapest International Research and Critics University, 2021)
This article describes the implementation of special autonomy (Ots) policies in Papua through the management of the Special Autonomy Fund by formulating a strategic plan for sustainable development. Strategic Planning Program and Other Programs for Sustainable Development to Initiate and Promote Development in Papua. The purpose of this study is to analyze and understand the procedures for managing the Special Autonomy Fund. The method used is qualitative by studying, interpreting, explaining, analyzing, and interpreting various forms of procedures for managing the Special Autonomy Fund for Papua's Sustainable Development. As a result, it appears that the Papua Special Autonomy Fund's operations are weak, community participation is small, and the budget is ineffective. When the Special Autonomy Fund was implemented, there were no irregularities in its use. However, Papuans feel that there is a lack of funds for special autonomy compared to the many demands and expectations of the people in this area. Therefore, the management of these funds must be transparent and honest, and the community must also be involved in the preparation of Papua's sustainable development programs.